A emergência do discurso da inclusão escolar na biopolítica: uma problematização em busca de um olhar mais radical - Pagni, Pedro Angelo (2017)
ABSTRACT The discourse on the inclusion statements formed in line with the current setting of biopolitics in neoliberalism, sometimes disregarding the dissonances generated by experience, the difference that highlights relations with disability and by the event that means at school. To recover these aspects, this article aims to discuss the form contained in the discourses about the inclusion and indicate another glimpse into the relationship with disability in educational contexts. To this end, we resorted to the afterthought of Michel Foucault to analyze some clues about the emergence and the limits of the discourses on school inclusion. To get another look at the subject we will focus on the positivity of disabilities in school and the need to move from discourse on the inclusion practices in which the relationship with the disabled lance the actors of this institution challenges of ethics differentiation and political positioning common.